Reduced Resting-State Functional Connectivity in Current and Recovered Restrictive Anorexia Nervosa - Scaife, Jessica Clare; Godier, Lauren Rose; Filippini, Nicola; Harmer, Catherine J.; Park, Rebecca J. (Frontiers in Psychiatry, 2017)
Abstract Functional connectivity studies based on resting-state functional magnetic resonance imaging (rs-fMRI) have shown alterations in brain networks associated with self-referential processing, cognitive control and somatosensory processing in Anorexia Nervosa (AN). This study aimed to further investigate the functional connectivity of resting-state networks (RSNs) in homogenous subsamples of individuals with restrictive AN (current and recovered), and the relationship this has with core eating disorder psychopathology. Rs-fMRI scans were obtained from twelve female patients with restrictive AN, fourteen females recovered from restrictive AN, and sixteen female healthy controls. Independent components analysis revealed a set of functionally relevant RSNs, previously reported in the literature. Dual regression analysis showed decreased temporal coherence in the lateral visual and auditory RSNs in individuals with current AN and those recovered from AN compared to healthy individuals. This decreased connectivity was found in regions associated with somatosensory processing, and is consistent with reduced interoceptive awareness and body image perception characteristic of AN. Widespread grey matter (GM) reductions were also found in the AN groups, and differences in functional connectivity were no longer significant when GM maps were added as a covariate in the dual regression analysis. This raises the possibility that deficits in somatosensory and interoceptive processing observed in AN may be in part underpinned or exacerbated by GM reductions.